Designing carbon dots for enhanced photo-catalysis: Challenges and opportunities - Zdrazil, Lukas; Cadranel, Alejandro; Medved‘, Miroslav; Otyepka, Michal; Zbořil, Radek; Guldi, Dirk Michael (Chem, 2024)
Carbon dots (CDs) are a fascinating class of nanomaterials with a straightforward design by means of an organic chemistry toolbox and an unsurmountable potential in the field of artificial photosynthesis. The vast structural diversity of CDs and the complex photo-physics thereof impose, however, significant challenges on their full utilization. Gathering a profound understanding of the structure-activity relationship and precise identification of the photo-catalytically active sites within CDs is crucial. This review summarizes the current understanding of photo-catalytically active CD-based systems. First, we analyze the structural complexity of CDs in the context of hydrogen photo-production, addressing the different roles of CDs in photo-catalytic hydrogen evolution as photosensitizers, co-catalysts, and catalysts. Second, we present the most important aspects to be considered for the design of CDs-based photo-catalysts, focusing on the fine-tuning of optical properties and charge management and discussing the timescales of events in the photo-excited state. Both experimental and theoretical methods relevant to studying structurally complex CDs are outlined. Finally, we share our thoughts on the future opportunities in CD-based photo-catalysis.
CRIS-Team Scopus Importer:2024-09-13
Keywords: carbon dots; functional materials; hydrogen production; photo-catalysis; SDG7: Affordable and clean energy; structure-property relationship